The complexity of forest bioethics - Arce-Rojas, Rodrigo Severo (2024)
The objective of this reflection article is to account for the complexity of the approach to forest bioethics among the actors involved in the Peruvian Amazon in a context dominated by an anthropocentric perspective and the neoliberal capitalist system. For this purpose, bibliographic research was carried out and complemented by the discussions generated around the forestry philosophy cycle developed by Forest Fridays, the Peruvian virtual training space for forestry engineers, between August and September 2022. From the results of the reflection, it is concluded that the approach to forest bioethics in the Peruvian forestry sector is incipient, made difficult by a strongly sectoral, disciplinary framework marked by the development paradigm based on neoliberal capitalism. Complexity helps to have a much broader vision and inscribes it in the current challenges of searching for alternatives to development that have in the full valuation of life, in all its manifestations, a new regenerative paradigm.